AHIMSA IN BASIC HINDU SCRIPTURES, WITH REFERENCE TO COSMO-ETHICS (ECOLOGY) John G. Arapura : . - Arapura , John G. (Journal of Dharma, 1991)
The word ahimsa is often translated as "non-violence," especially owing to its use in the modern times as a method of social and political struggles. This translation like others such as non-hurting. Non-killing, non-lnlurv, etc., are no doubt correct, but like them it expresses only one of this word’s many imports. This issue of the Journal of Dharma is an attempt to focus on a paramount meaning of the word that has to do with the non-destruction, and hence caring preservation. of all forms of life upon our planet. aconcern whose urgency is being felt more and more acutely as days go by. Hence we couple ahimsii with ecology.